Playing with the boys : why separate is not equal in sports - McDonagh, Eileen L. (Oxford University Press, 2008)
"In this forcefully argued book, Eileen McDonagh and Laura Pappano show in vivid detail how women have been unfairly excluded from participating in sports on an equal footing with men. Using powerful examples from the world of contemporary American athletics - girls and women trying to break through in football, ice hockey, wrestling, and baseball to name just a few - the authors show that sex differences are not sufficient to warrant women's coercive exclusion from competing with men; that some sex-group difference actually confer a sports advantage to women; and that "special rules" for women in sports do not simply reflect the "differences" between the sexes, but actively create and reinforce a view that women as a group are inherently inferior to men - even when women clearly are not. For instance, women's bodies give them a physiological advantage in endurance sports like the ultra-marathon and distance swimming. So, why do many Olympic events - from swimming to skiing to running to bike racing - have shorter races for women than men? Likewise, why are women's tennis matches limited to three sets while men's are best-of-fives? This book shows how sex-segregated sports policies, instead of reflecting sex-group differences, in fact construct them."--Jacket